2010
DOI: 10.47102/annals-acadmedsg.v39n9p670
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Management of Surgical Upper Limb Infections in Patients with End-stage Renal Failure

Abstract: Introduction: Hand infections in patients with end-stage renal failure (ESRF) are more difficult to treat and have had the worse outcomes. This paper examines the epidemiology, bacteriology and outcomes of surgically managed upper limb infections in these vulnerable patients. Materials and Methods: All patients from a single centre with surgically-managed upper limb infections between 2001 and 2007 were reviewed. We collected epidemiological data on demographics, type and site of infection, bacteriology, surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Diabetes is often seen as a comorbidity along with renal disease. Xu et al found it was the cause of renal failure in 88% of ESRD patients who underwent upper extremity infection surgical debridement [ 15 ]. Patients with renal disease and diabetes demand extra consideration, and prospective studies are needed to determine the safest course of treatment for this complex group.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is often seen as a comorbidity along with renal disease. Xu et al found it was the cause of renal failure in 88% of ESRD patients who underwent upper extremity infection surgical debridement [ 15 ]. Patients with renal disease and diabetes demand extra consideration, and prospective studies are needed to determine the safest course of treatment for this complex group.…”
Section: Discussionmentioning
confidence: 99%